The Influence of Digital Sharia Banking Services on the Digital Financial Literacy of Generation Z in Malang City - Shalshabilla Putri; Rini Safitri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this research is to determine the influence of digital sharia banking services on the digital financial literacy of generation z in Malang City. This study including in type study quantitative. Object for this study is generation z in Malang City consisting of from 100 respondents . Retrieval technique sample use technique purposive sampling. Data collection techniques through spread questionnaires and for technique data analysis using simple regression analysis​​ linier with SPSS software. The variables studied​ are Digital Services (X) and Digital Financial Literacy (Y). The research results show that digital services provided by sharia banking have a significant and positive effect on the digital financial literacy of generation z in Malang City. It means that every additional digital sharia banking service can increase the digital financial literacy of generation z in Malang City.